Influence of homoarginine on creatine accumulation and biosynthesis in the mouse - Lygate, Craig A.; Lake, Hannah A.; McAndrew, Debra J.; Neubauer, Stefan; Zervou, Sevasti (Frontiers in Nutrition, 2022)
Organisms obtain creatine from their diet or by de novo synthesis via AGAT (L-arginine:glycine amidinotransferase) and GAMT (Guanidinoacetate N-methyltrasferase) in kidney and liver, respectively. AGAT also synthesises homoarginine (hArg), low levels of which predict poor outcomes in human cardiovascular disease, while supplementation maintains contractility in murine heart failure. However, the expression pattern of AGAT has not been systematically studied in mouse tissues and nothing is known about potential feedback interactions between creatine and hArg. Herein, we show that C57BL/6J mice express AGAT and GAMT in kidney and liver respectively, whereas pancreas was the only organ to express appreciable levels of both enzymes, but no detectable transmembrane creatine transporter (Slc6A8). In contrast, kidney, left ventricle (LV), skeletal muscle and brown adipose tissue must rely on creatine transporter for uptake, since biosynthetic enzymes are not expressed. The effects of creatine and hArg supplementation were then tested in wild-type and AGAT knockout mice. Homoarginine did not alter creatine accumulation in plasma, LV or kidney, whereas in pancreas from AGAT KO, the addition of hArg resulted in higher levels of tissue creatine than creatine-supplementation alone (P<0.05). AGAT protein expression in kidney was downregulated by creatine supplementation (P<0.05), consistent with previous reports of end-product repression. For the first time, we show that hArg supplementation causes a similar down-regulation of AGAT protein (P<0.05). These effects on AGAT were absent in the pancreas, suggesting organ specific mechanisms of regulation. These findings highlight the potential for interactions between creatine and hArg that may have implications for the use of dietary supplements and other therapeutic interventions.